A BOOK REVIEW ARTICLE: P. D. JAMES THE LIGHTHOUSE: A RECONSTITUTION OF ENGLISH CLASSIC MYSTERY INGREDIENTS - Jacob George (Celt: A Journal of Culture, English Language Teaching & Literature, 2006)
THE LIGHTHOUSE P.D. JAMES London: Faber, 2005, 400 pp. ISBN: 0-307-26291-X